Fabrication of Anti-glaucoma Nanofibers as Controlled-Release Inserts for Ophthalmic Delivery of Brimonidine Tartrate: In Vivo Evaluation in Caprine Eye - Fariba Shaikhi Shoushtari; Mohammadshakib Naghshbandy; Leila Rezaei; Saba Mehrandish; Shahla Mirzaeei (Advanced Pharmaceutical Bulletin)
Purpose: Chronic ailments usually decrease the quality of life due to the requirement for repetitive administration of drugs. Glaucoma is a chronic eye disease occurred because of increased intraocular pressure (IOP). Controlled-release inserts can overcome this challenge by a gradual release of the antiglaucoma drugs. This study aimed to fabricate ocular inserts of brimonidine tartrate (BMD) for the management of glaucoma. Methods: Different polymers including poly (D, L-lactide), polycaprolactone, cellulose acetate, and Eudragit RL100® were used to develop the BMD-loaded nanofibrous inserts by electrospinning technique. The inserts were characterized. The morphology and drug-polymer compatibility were examined by scanning electron microscopy (SEM), and Fourier-transform infrared (FTIR) spectroscopy and in vitro drug release in PBS. The IOP-lowering efficacy and irritancy of optimized formulation were assessed in the caprines. Results: SEM images demonstrated nanofibers with uniform morphology and a mean diameter<300 nm were fabricated. The nanofibers were high-strength and flexible enough to be placed in the conjunctival sac. FTIR showed drug-polymer compatibility. In vitro release study indicated a sustained-release profile of the drug during 6 days for inserts. In vivo evaluation indicated that the optimized formulation is capable of maintaining the IOP in a non-glaucomatous range for an extended duration of 6 days. In addition, the formulation was non-irritant to the caprine eye. Conclusion: Due to the prolonged IOP-lowering efficiency, BMD-loaded nanofibrous inserts can be considered suitable for the controlled release of drugs and thus enhance patient compliance by reducing the frequency of administration.